Stair evacuation of people with mobility impairments. (23rd April 2014) - Kuligowski, Erica; Peacock, Richard; Wiess, Emily; Hoskins, Bryan; Boyce, Karen
Summary This paper presents data on the movement speeds of occupants with various types of mobility impairments evacuating two residential facilities for older adults located on the East Coast of the USA with the goal of better understanding of behavior and movement speeds during stairwell evacuation with and without assistance. The building populations who took part in the current study comprised a diverse array of older adults and disabled residents descending the stairwells by the following methods: self‐evacuation without assistance, assistance using a cane, assistance from another occupant or firefighter, or assistance using a stair chair. Movement data of these specific groups were compared and contrasted with other data collected on mobility‐impaired individuals. In the current study, the National Institute of Standards and Technology observed overall average speeds of 0.31 ± 0.16 m/s (with individual speeds ranging from 0.07 to 0.91 m/s), which in some cases, approximate the speeds of disabled people and older adults found in earlier studies, and in other cases are slower than those observed in previous studies. Slower speeds reported here may have resulted from observing a wider variety of mobility impairments (because one of the buildings observed was an assisted‐living facility) and from evacuation assistance provided by untrained populations. These data provide an adequate confirmation of exiting literature values typically used for disabled movement speeds in addition to updated values for future analyses. Copyright © 2014 John Wiley & Sons, Ltd.